Respiratory symptoms and ventilatory function among granite workers working in quarries installed with mechanical crushers in and around Kandy Municipality limits - P Jayawardana; S Tennakoon; V Bandara (College of Community Physicians of Sri Lanka, 2011)
Objectives: To compare the presence of selected respiratory symptoms among granite workers with a control group and to assess ventilatory function (VF) and radiological changes in the lungs of granite workers. Methods: A cross-sectional analytical study was conducted on workers employed in the granite quarries in-stalled with mechanical crushers in and around the Kandy Municipality limits. The control group comprised persons accompanying patients to the outpatient department of a tertiary care hospital. The respiratory symptoms were compared using an interviewer administered questionnaire. Only granite workers were subjected to spirometry and chest radiography. Forced vital capacity (FVC), forced expiratory volume in the first second of FVC and peak expiratory flow rate were assessed. The observed values of above were compared with predicted normal values. Chest radiographs were read by two radiologists conforming to ILO classification of radiographic appearances. Results: There were 51 granite workers and 51 controls. A higher proportion of granite workers had chronic cough (8%; n=4), and phlegm (16%; n=8) of ≥3 months duration and chronic bronchitis (16%; n=8) in comparison to the control group (2% [n=1], 6% [n=3] and 8% [n=4] respectively) but the differences were statistically not significant. A significantly higher proportion in the control group had dyspnoea (45%; n=23) and at least a single respiratory symptom (55%, n=28) in comparison to the granite workers (10% [n=5] and.31% [n=16] respectively). The observed values of the three respiratory indices were significantly lower than the predicted norms. Twenty four (47%) had a restrictive type and one (2%) an obstructive type of ventilatory impairment. None had radiological evidence of silicosis or tuberculosis. Conclusions: Ventilatory function of granite workers were affected significantly. Proportions with cough and phlegm of equal or more than three months duration and chronic bronchitis were higher among granite workers even though statistical significance was not reached. Proportions with dyspnoea and at least one respiratory symptom was significantly less among granite workers. There was no radiological evidence of silicosis or tuberculosis. Installation of exhaust ventilation, use of industrial masks and limitation of exposure time is recommended. Key Words: Granite workers; Ventilatory impairment; Respiratory symptoms DOI: 10.4038/jccpsl.v13i2.2963 Journal of the College of Community Physicians of Sri Lanka Vol.13(2) 2008 9-16